2014
DOI: 10.1137/130938232
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Model Equation in Detonation Theory

Abstract: Here we analyze properties of an equation that we previously proposed to model the dynamics of unstable detonation waves [A. R. Kasimov, L. M. Faria, and R. R. Rosales, Model for shock wave chaos, Phys. Rev. Lett., 110 (2013), 104104]. The equation is utIt describes a detonation shock at x = 0 with the reaction zone in x < 0. We investigate the nature of the steady-state solutions of this nonlocal hyperbolic balance law, the linear stability of these solutions, and the nonlinear dynamics. We establish the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 43 publications
5
35
0
Order By: Relevance
“…In this section, we investigate the one-dimensional traveling wave solutions of (2.3-2.4), as well as their stability properties. Note that, since in the one-dimensional case the proposed system reduces to equation (2.1), the traveling wave solutions are identical to those found in [5]. For completeness, we briefly repeat the discussion here.…”
Section: Traveling Wave Solutions and Stability Analysismentioning
confidence: 56%
See 2 more Smart Citations
“…In this section, we investigate the one-dimensional traveling wave solutions of (2.3-2.4), as well as their stability properties. Note that, since in the one-dimensional case the proposed system reduces to equation (2.1), the traveling wave solutions are identical to those found in [5]. For completeness, we briefly repeat the discussion here.…”
Section: Traveling Wave Solutions and Stability Analysismentioning
confidence: 56%
“…The importance of this latter development stems from the fact that unsteadiness is a common feature of gaseous detonations. Along the same lines of analog modeling, in [13,5] we have shown that even a scalar forced Burgers equation contains all the ingredients necessary to reproduce the complexity of one-dimensional detonations, including complicated chaotic solutions. Importantly, all the prior work with analog models is limited to one-dimensional descriptions.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…It was also shown in [4] using detonation analogies that the resolution of the chemical reaction zone associated with a pulsating DW is a challenging problem even in the one-dimensional statement because the size of the reaction zone varies by orders of magnitude in the process of pulsations due to the occurrence of local explosions behind the LW front. The issue of a sufficient level of resolution of the chemical reaction zone in numerical experiments on the DW propagation using shock capturing schemes remains open, and the number of papers devoted to this problem is steadily increasing (e.g., see the references in [3]).…”
Section: N E Rtmentioning
confidence: 99%
“…The Fickett model [13] has subsequently motivated various extensions and modifications [34,43,25,10,12,9]. The principal aim of all of these works is to identify a minimal model that is capable of reproducing the rich set of dynamical properties of the full system of the reactive Euler equations.…”
Section: Introductionmentioning
confidence: 99%